Natural outcrossing in common bean in Costa Rica. - Chaves-Barrantes, Néstor Felipe; Araya-Villalobos, Rodolfo; Debouck, Daniel G. (Agronomía Mesoamericana, 2014)
The objective of the research was to evaluate the natural outcrossing rate between two varieties of common bean in Alajuela and Fraijanes, localities in the Central Valley of Costa Rica. The experimental plot included three blocks with ten 15.0 m long rows, 0.8 m The black-seeded varieties UCR 55 and Guaymí were growing in Fraijanes and Alajuela in the central block respectively; while the white-seeded variety PAN 68 was planted in the two lateral blocks. The experiments were carried out from 2002 thru 2003 in Fraijanes and from 2002 thru 2007 in Alajuela. The variables: wind direction, seasonal effect and distance from the pollen source were evaluated. There was a synchrony in the flowering time of the varieties in both localities. All plants of the white-seeded variety were numbered and harvested in the five nearest rows to the black-seeded varieties. Natural outcrossing was recorded as a percentage of seedlings with purple hypocotyl in the F1 progeny of PAN 68 (variety that shows green hypocotyls). In Alajuela the rate of natural outcrossing varied from 0,000 to 0.096%, while in Fraijanes it did from 0.004 to 0.033%. The general allogamy was of 0.031%, a lower outcrossing if compared to trials carried out in other countries. The natural outcrossing was not affected by the dry or rainy season nor the wind direction, but it was inversely affected by the distance from the pollen source in Alajuela (r2=0.9622, p≤0.05); It was nil from 4 m away from the pollen source.